Incentives and drivers for private embedded generation through solar photovoltaic systems in South Africa - Louie van Schalkwyk; Michelle Scholtz (Frontiers in Environmental Economics)
Renewable energy generation, especially in the form of rooftop solar photovoltaic (PV) systems, is expected to play an important role in South Africa's future energy mix. The national government, along with various municipalities at local government level, are introducing regulatory incentives to promote the uptake of solar PV systems in the private sector. These incentives include feed-in tariffs, capital subsidies and tax benefits. In addition to the regulatory incentives, there are non-regulatory drivers that motivate private property owners to pursue solar PV systems. These drivers include environmental considerations, cost savings, energy security, tenant requirements, and green-energy finance. This study examines the various regulatory incentives to pursue solar PV systems available to private property owners located in the City of Cape Town Metropolitan Municipality. The City of Cape Town is selected as a single case-study area as the municipality creates a conducive environment through its regulatory framework for private property owners to pursue private embedded generation systems. The study examines the different incentives applicable to residential and non-residential property owners. The research also establishes to what extent the regulatory incentives influence private property owners to pursue solar PV systems compared to non-regulatory drivers and benefits. The study reveals that the various regulatory incentives differ for residential and non-residential property owners. These differences impact the extent to which the regulatory incentives motivate particular private property owners to pursue solar PV systems. The research suggests that, although regulatory incentives play a role in private property owners' decision-making process, the non-regulatory drivers are the main motivating factors for private property owners pursuing solar PV systems.